2018
DOI: 10.1177/0001839218804527
|View full text |Cite
|
Sign up to set email alerts
|

Subordinate Activation Tactics: Semi-professionals and Micro-level Institutional Change in Professional Organizations

Abstract: This two-year ethnographic study of the primary care departments in two U.S. hospitals examines how managers can bring about micro-level institutional change in professional practice even when such change challenges professionals’ specialized expertise, autonomy, individual responsibility, and engagement in complex work, which previous research has shown to create difficulties. In this study, managers in both hospitals attempted to implement the same patient-centered medical home (PCMH) reforms among doctors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 139 publications
(189 reference statements)
1
46
0
Order By: Relevance
“…This study also makes a number of contributions to scholarship on influence among low-power groups in organizations. While prior research on issue selling, low-power occupations, and upward influence has detailed a host of tactics and processes for attaining influence in organizations (e.g., Mechanic, 1962; Schilit and Locke, 1982; Ashford et al, 1998; Dutton et al, 2001; Kellogg, 2018), the peripheral experts studied here did not have basic access to, knowledge of, or a means by which to establish trust with line managers in daily work and thus had to employ different tactics focused on achieving these basic relational resources. Prior research has been conducted on influencers and targets who likely already have existing relationships or fairly easy ways to develop them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also makes a number of contributions to scholarship on influence among low-power groups in organizations. While prior research on issue selling, low-power occupations, and upward influence has detailed a host of tactics and processes for attaining influence in organizations (e.g., Mechanic, 1962; Schilit and Locke, 1982; Ashford et al, 1998; Dutton et al, 2001; Kellogg, 2018), the peripheral experts studied here did not have basic access to, knowledge of, or a means by which to establish trust with line managers in daily work and thus had to employ different tactics focused on achieving these basic relational resources. Prior research has been conducted on influencers and targets who likely already have existing relationships or fairly easy ways to develop them.…”
Section: Discussionmentioning
confidence: 99%
“…Second, scholars of work and occupations have found that lower-power occupational groups in organizations (e.g., nurses) can sometimes elicit cooperation from higher-power groups (e.g., physicians) by making the high-power groups dependent on them (Emerson, 1962; Mechanic, 1962; Pfeffer, 1992; Kellogg, 2018), such as by becoming more central to the workflow (Allen, 1997), developing superior skills or knowledge (Hughes, 1988; Barley and Bechky, 1994; Black, Carlile, and Repenning, 2004), or controlling objects key for work completion (Crozier, 1964; Bechky, 2003; Zuzul, 2018). In all these cases, however, low-power occupational group members were also part of the core line function of the organization (unlike peripheral experts) and were able to use their proximity to the core to gain access to and knowledge of their influence targets.…”
Section: Influence By Low-power Groups In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 5. We further iterated between our derived higher-order themes, our codes, and our data until we had induced the simplest set of concepts that could explain our observations (Glaser and Strauss, 1967;Kellogg, 2018). We also drew on prior literature to understand not only how these concepts functioned in our cases but also their more abstract mechanisms.…”
Section: Data Analysis Proceduresmentioning
confidence: 99%
“…Interestingly, new terminology around organizational behavior and new constructs in managing organizational change are already emerging. An example is a piece of inquiry discussed by Katherine Kellogg (2018) is "subordinate activation tactics" in the health care industry-actions fostering change in professional practice by lowerlevel employees.…”
mentioning
confidence: 99%